2022
DOI: 10.3390/genes13111996
|View full text |Cite
|
Sign up to set email alerts
|

Migration/Differentiation-Associated LncRNA SENCR rs12420823*C/T: A Novel Gene Variant Can Predict Survival and Recurrence in Patients with Breast Cancer

Abstract: Long non-coding RNAs (lncRNAs) have key roles in tumor development and the progress of many cancers, including breast cancer (BC). This study aimed to explore for the first time the association of the migration/differentiation-associated lncRNA SENCR rs12420823C/T variant with BC risk and prognosis. Genotyping was carried out for 203 participants (110 patients and 93 controls) using the TaqMan allelic discrimination technique. The corresponding clinicopathological data, including the recurrence/survival times,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Interestingly, in their review article, Minotti et al stated that MALAT1and MIAT presented a higher number than expected of function-impacting somatic mutations, and they confirmed that the single-nucleotide polymorphisms (SNPs) of lncRNAs might play a role in carcinogenesis, supporting their use as genetic biomarkers [28]. Several studies have highlighted the association between the genetic variants and SNPs that occur in regions transcribed into the lncRNAs and increase the risk and/or progression of cancers [29][30][31][32][33][34][35][36]. These SNPs may influence lncRNA regulation and the process of splicing and/or stability, resulting in the modification of its interacting partners, and thus they could be correlated with tumorigenesis [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in their review article, Minotti et al stated that MALAT1and MIAT presented a higher number than expected of function-impacting somatic mutations, and they confirmed that the single-nucleotide polymorphisms (SNPs) of lncRNAs might play a role in carcinogenesis, supporting their use as genetic biomarkers [28]. Several studies have highlighted the association between the genetic variants and SNPs that occur in regions transcribed into the lncRNAs and increase the risk and/or progression of cancers [29][30][31][32][33][34][35][36]. These SNPs may influence lncRNA regulation and the process of splicing and/or stability, resulting in the modification of its interacting partners, and thus they could be correlated with tumorigenesis [37][38][39].…”
Section: Introductionmentioning
confidence: 99%